Combination therapy with nicotinamide and tetracyclines for cicatricial pemphigoid: further support for its efficacy. - Reiche, L; Wojnarowska, F; Mallon, E (Blackwell Publishing Ltd., 1998)
We have previously reported the reduction of cicatricial pemphigoid orodynia with minocycline. Tetracycline combined with high dose nicotinamide has also been beneficial in a number of cutaneous immunological disorders. We now report a series of eight cases in whom further subjective or clinical improvement accrued in five, after the addition of high dose (2.5 or 3 g) nicotinamide to minocycline; however, one of these then discontinued the nicotinamide because of headache and nausea, another was withdrawn from the study because of progressive upper respiratory tract mucosal involvement, and two were changed from minocycline to tetracycline because they developed minocycline-induced hyperpigmentation.